The Effect of Compressor Speed ​​on Residential Air Conditioning Systems Using R407c and R32 Refrigerant - SAFRIL SAFRIL; Wan Azmi Bin Wan Hamzah; Teh Ting Wei; Ridho Hans Gurning; Sukarman Sukarman; Khoirudin Khoirudin (Jurnal Teknik Mesin Mechanical Xplore, 2025)
The demand for residential air conditioning (RAC) systems is expected to increase in the future owing to rising ambient temperatures resulting from global warming. Therefore, it is important to develop and study refrigerants that can improve energy efficiency and thermodynamic performance. This study compares R32 and R407c refrigerants in RAC systems, with an emphasis on the coefficient of performance (COP) and cooling capacity. The research methodology used an experimental approach by testing compressor speeds of 2400, 2700, and 3000 rpm. Based on the test results, R32 consistently performed better than R407c at all compressor speed variations. The COP and cooling capacity of R32 increased significantly by 15.53% and 35.90%, respectively. The stability of R32 performance operated at different compressor speed variations showed an increase in operational adaptability. Finally, R32 was proven to be a more effective and efficient refrigerant than R407c in the RAC system.